TAPPING THE PATHOGENIC BACTERIA FROM HOSPITAL WATER TAP SYSTEM IN MALAYSIA USING FLONGLE NANOPORE - U.A. Zainulabid; S. Wei; N. Kamarudin; P. Periyasamy; H.F. Ahmad (International Journal of Infectious Diseases, 2023)
Intro: The hospital water supply is a reservoir of nosocomial infection that is often neglected. Mounting studies showed that disease transmission in hospitals is caused by the pathogenic bacteria in the water system that carry antibiotic resistance genes (ARGs). Hence, this study was conducted as infection surveillance in monitoring disease transmission. Methods: We employed whole-genome sequencing techniques using Flongle flow-cell on the Oxford Nanopore Technologies platform to analyse the pathogenic bacteria isolated from tap water in an intensive care unit at Sultan Ahmad Shah Medical Centre @ IIUM. The obtained genome was annotated using the RAST tool kit (RASTtk) and pathogenicity analysis was performed using ResFinder and Pathogen Finder, respectively. This research was supported in full with Kurita Asia Research Grant (grant number 21Pmy021) provided by Kurita Water and Environment Foundation. Findings: Here, we obtained Pseudomonas aeruginosa and Stenotrophomonas maltophilia strains comprising 6,674,687 bp and 4,508,936 bp genome size. We estimated that both genomes contained around 66.0 to 66.5% of GC content. Both isolates harbouring beta lactam resistance genes. While Stenotrophomonas maltophilia harbouring blaL1, the Pseudomonas aeruginosa carries blaPAO and blaOXA-50 genes. Discussion: Based on the presence of the predicted ARGs, we speculated that the Stenotrophomonas maltophilia confer metallo-β-lactamase resistance, and the Pseudomonas aeruginosa will exhibit chromosomal-encoded cephalosporinase and oxacillinase phenotypes, respectively. Conclusion: Of critical importance, this research will help to understand the magnitude of nosocomial waterborne infections and support the holistic approach to carefully implementing antibiotic stewardship in hospital settings.